Needle tract seeding following core biopsies in retroperitoneal sarcoma. Issue 9 (September 2017) - Van Houdt, W.J.; Schrijver, A.M.; Cohen-Hallaleh, R.B.; Memos, N.; Fotiadis, N.; Smith, M.J.; Hayes, A.J.; Van Coevorden, F.; Strauss, D.C.
Abstract: Background: Retroperitoneal tumours often require a preoperative core needle biopsy to establish a histological diagnosis. Literature is scarce regarding the risk of biopsies in retroperitoneal sarcomas, so the aim of this study is to identify the potential risks of core needle biopsies causing needle tract recurrences or local recurrences. Method: Patients who underwent resection of a primary retroperitoneal sarcoma between 1990 and 2014 were identified from a prospectively maintained database from two tertiary referral centres. Patient demographics, tumour characteristics and biopsy techniques were examined. The primary endpoint was needle tract recurrence and local intra-abdominal recurrence. Results: 498 patients were included in the analysis. The most common histological subtypes were liposarcoma (66%) and leiomyosarcoma (18%). Of the 498 patients that underwent resection, 255 patients were diagnosed with a preoperative biopsy. Five patients (2%) developed a biopsy site recurrence: 3 patients with leiomyosarcomas and 2 patients with dedifferentiated liposarcomas. All biopsy site recurrences occurred after trans-abdominal biopsies and were not performed with a co-axial technique. There was no significant difference in local recurrence rate between the patients with or without a biopsy (=0.30) or for the biopsy route (trans-abdominal or trans-retroperitoneal (p = 0.72)). Conclusion: The risk of a needle tract metastasis after core needle biopsy for retroperitoneal sarcoma is very low but not zero. The safest method seems a trans-retroperitoneal approach with a co-axial technique. Local recurrence rate is not altered after doing a core needle biopsy.